Cervical Paraganglioma Mimicking Thyroid Nodule: A Rare Clinical Case - Berna İmge Aydoğan; Serpil Dizbay Sak; Sevim Güllü (Case Reports in Endocrinology)
Objective. Paraganglioma is a rare neuroendocrine tumor. When it is located in the neck, it is commonly misdiagnosed as other thyroid neoplasms. Case Report. We report a case of cervical paraganglioma in a 55-year-old female. Patient was admitted to our clinic with goiter and neck pain. Thyroid ultrasonography revealed a 20 mm solitary, heterogeneous nodule located in the upper pole of left thyroid lobe. Fine needle aspiration cytology was nondiagnostic. She underwent left lobectomy and histopathology showed paraganglioma. Discussion. Cervical paragangliomas should be considered in the differential diagnosis of thyroid nodules.